(untitled) (Bangladesh Journal of Anatomy, 2014)
Context: Mandible is the lower jaw bone providing attachment of muscles of mastication and facial expression and provides pathway for inferior alveolar nerve and vessels. Adequate anaesthesia is a prerequisite of most of the dental procedures. Effective pain control in dentistry may be achieved by the local anaesthetic techniques; the most common procedures which are followed by the inferior alveolar nerve block. Therefore, identification of mandibular foramen is important for dental surgeons in nerve block and surgical procedures to avoid injury to neurovascular bundle. The aim of this study was to determine the position of the mandibular foramen from various anatomical landmarks. Materials and Methods: A cross sectional analytical type of study was carried out in the department of Anatomy, Dhaka Medical College, Dhaka on one hundred and eighty five (185) dry adult human mandibles of unknown sex. Position of mandibular foramen was determined using the distance of the mandibular foramen to (a) the anterior border of the ramus (b) the posterior border of the ramus (c) the mandibular notch (d) the head of the mandible (e) the posterior edge of third molar socket and (f) the symphysis menti which were measured with the help of digital sliding calipers. Results: The mandibular foramen was at the same distance from each landmark on both sides demonstrating symmetry. There was no significant difference in the values on the right and left sides of the mandibles. Conclusion: Anatomical knowledge of this study might be useful in certain surgical procedure. DOI: http://dx.doi.org/10.3329/bja.v11i2.20671 Bangladesh Journal of Anatomy, July 2013, Vol. 11 No. 2 pp 58-61